Otimização do cultivo de Lasiodiplodia theobromae para obtenção de EPS e caracterização física e química dos polissacarídeos - Oliveira, Kassandra Sussi Mustafé [UNESP] (2014)
Lasiodiplodia theobromae is phytopatogenic fungus causing gumnosis in plant species that are widely distributed in Brazil. This fungus produces exopolysaccharide (EPS) but its chemical structure is not completely defined. Furthermore, the studies of fermentation in defined medium and parameters in bioreactor cultures are still limited. This work describes the optimization using Response Surface Methodology (RSM) in orbital shaker, an aeration study in stirred-tank bioreactor, an early rheological characterization of fermentation broths, and also a refined structure evaluation from the EPS produced by L. theobromae MMBJ. The polysaccharides from mycelia were also described. Fractionated and purified EPS show the presence of three different glucans. One of them, a chilled water insoluble β-(1→3)-(1→6)- glucan, was the EPS with higher yield (67% w/w). The other two are soluble β-(1→6)- glucans, one with 7×103 g/mol and the other with 1.8×106 g/mol. The glucan with higher molecular weight is the largest β-(1→6)-glucan described and can be applied for pharmaceutical uses, since immunomodulatory effects are usually associated with molecular weight. Commercial sucrose and Ammonium nitrate were chosen among carbon (pure sucrose, commercial sucrose, glucose, fructose, lactose or sugar cane molasses) and nitrogen sources (ammonium nitrate, ammonium phosphate, sodium nitrate or urea) as most suitable for EPS biosynthesis. The Box-Behnken design using RSM showed that 56.6 g/L of commercial sucrose and 2.03 g/L of ammonium nitrate is the formulation that promotes EPS synthesis. This medium formulation was also used in bioreactor at 0.8 vvm or 1.5 vvm (agitation set at 300 rpm). The lower aeration rate promoted EPS synthesis, confirmed by the maximum EPS concentration obtained (7.35 g/L) after 72 hours. From total EPS amount, 1.8 g/L were β-(1→6)-glucans and 5.5 g/L were β-(1→3)-(1→6)-glucan. Differently, cultures at 1.5 vvm...